Action history influences eye movements. Issue 5 (28th May 2018) - Weidler, Blaire J.; Suh, Jihyun; Abrams, Richard A.
ABSTRACT: Recent research has revealed that simple actions can have a profound effect on subsequent perception – people are faster to find a target that shares features with a previously acted on object even when those features are irrelevant to their task (the action effect ). However, the majority of the evidence for this interaction between action and perception has come from manual response data. Therefore, it is unknown whether action affects early visual search processes, if it modulates post-attentional-selection processes, or both. To investigate this, we tracked participants' spontaneous eye movements as they performed an action effect task. In two experiments we found that participants looked more quickly to the colour of an object they had previously acted on, compared to if they had viewed but not acted on the object, showing that action influenced early visual search processes. Additionally, there was evidence for post-selection effects as well. The results suggest that prior action affects both pre-selection and post-selection processes – spontaneously guiding attention to, and maintaining it on, objects that were previously important to the observer.